Therapeutic Music in the Aeromedical Transport of Critically Ill Patients: Intervention to Reduce Flight Stressors (Global Journal of Medical Research, 2022)
Therapeutic music is one of the strategies widely adopted as a complementary therapy, proven by its relevance as a strategy to reduce pain, decrease the level of anxiety and increase adherence to treatment, especially in critically ill hospitalized patients. The application of complementary practices in critically ill patients has been introduced in many Intensive Care Units (ICU) as their benefits are evidenced both in biopsychosocial well-being and in the spiritual sphere. This work is a survey of articles whose objective was to characterize the scientific production on the application of Music Therapy. The main search source was in the databases indexed in the Biblioteca Virtual de Saúde (BVS) and Scientific Electronic Library Online (SciELO). In order to reduce the damage caused by painful procedures and the permanence in an exhausting environment such as the ICU, full of alarms, lights and other noises, many professionals seek a way to humanize through various integrative and non-pharmacological therapies.
Keywords: air medical transport; music therapy; integrative therapies